Colleters, Extrafloral Nectaries, and Resin Glands Protect Buds and Young Leaves of Ouratea castaneifolia (DC.) Engl. (Ochnaceae) - Elder A. S. Paiva; Gabriel A. Couy-Melo; Igor Ballego-Campos (Plants, 2021)
Buds usually possess mechanical or chemical protection and may also have secretory structures. We discovered an intricate secretory system in Ouratea castaneifolia (Ochnaceae) related to the protection of buds and young leaves. We studied this system, focusing on the distribution, morphology, histochemistry, and ultrastructure of glands during sprouting. Samples of buds and leaves were processed following the usual procedures for light and electron microscopy. Overlapping bud scales protect dormant buds, and each young leaf is covered with a pair of stipules. Stipules and scales possess a resin gland, while the former also possess an extrafloral nectary. Despite their distinct secretions, these glands are similar and comprise secreting palisade epidermis. Young leaves also possess marginal colleters. All the studied glands shared some structural traits, including palisade secretory epidermis and the absence of stomata. Secretory activity is carried out by epidermal cells. Functionally, the activity of these glands is synchronous with the young and vulnerable stage of vegetative organs. This is the first report of colleters and resin glands for O. castaneifolia. We found evidence that these glands are correlated with protection against herbivores and/or abiotic agents during a developmental stage that precedes the establishment of mechanical defenses.